Replacing the Sovereign Subject with savoir - Tiisala, Tuomo (Power and Freedom in the Space of Reasons, 2024)
This chapter reviews in exegetical detail how Foucault replaces the Sovereign Subject with savoir as the basis of discursive cognition. Foucault never explains how individuals acquire savoir, however, but in this respect, accounts of linguistic training by Wittgenstein and Sellars might be used as a helpful supplement. The continuity between those accounts and Foucault's view of savoir is established by showing that the formation of concepts in The Archaeology of Knowledge is explained in terms of rule-governed patterns of language-use in discourse as a social practice. Furthermore, this perspective into Foucault's philosophy provides additional resources to address the common criticism that it involves an incoherent account of the subject as both essentially dependent on relations of power and endowed with a capacity for autonomy.